2014
DOI: 10.2139/ssrn.2445370
|View full text |Cite
|
Sign up to set email alerts
|

What Drives Bilateral Remittances to Pakistan? A Gravity Model Approach

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 57 publications
2
5
0
Order By: Relevance
“…Considering whether banking sector development (BSD) is a major determinant of migrant remittances flows, the long-run estimates show that the coefficient of BSD is positive and significant at 1% suggesting that BSD is a significant driver of migrant remittances flows in the region. These results are in line with previous works (Ahmed and Martinez-Zarzoso, 2014;Panda and Trivedi, 2015;Heffernan, 2018;Onwuka, 2019;Omon, 2021) who affirmed that banking sector development and equity market development are key determinants of migrant remittances. The implication of this outcome is that the existence of a developed financial market tends to drive migrant remittances into the region.…”
Section: Panel Regression Estimatessupporting
confidence: 93%
“…Considering whether banking sector development (BSD) is a major determinant of migrant remittances flows, the long-run estimates show that the coefficient of BSD is positive and significant at 1% suggesting that BSD is a significant driver of migrant remittances flows in the region. These results are in line with previous works (Ahmed and Martinez-Zarzoso, 2014;Panda and Trivedi, 2015;Heffernan, 2018;Onwuka, 2019;Omon, 2021) who affirmed that banking sector development and equity market development are key determinants of migrant remittances. The implication of this outcome is that the existence of a developed financial market tends to drive migrant remittances into the region.…”
Section: Panel Regression Estimatessupporting
confidence: 93%
“…The complementarity hypothesis urge that the development financial sector would reduce transaction costs and positively affect remittances inflow; whereas, the substitutability hypothesis ascertains that the workers' remittances and financial development of the home country are negatively associated. The empirical studies on Pakistan have revealed a significant positive effect of financial development validating complementarity proposition,(Ahmed and Martinez-Zarzoso 2014;and Umair and Waheed 2017).…”
mentioning
confidence: 88%
“…The economic conditions in the host countries play an important role in international migration and remittance outflow. The literature on remittances has concluded a significant positive effect of host countries' economic condition and remittances inflow to Pakistan, (Abbas, 2016;Ahmed and Martinez-Zarzoso 2014;and Umair and Waheed 2017). The economic performance of GCC countries despite continuous efforts of diversification, dependent on the demand for crude oil and oil prices.…”
Section: Review Of Literaturementioning
confidence: 99%
“…While just over 2 million Pakistanis are working and living in Saudi Arabia, close to 2.7 million Indians live in the kingdom. Pakistan’s total remittances from abroad stand are close to US$20 billion per annum, out of which approximately US$6 billion come from Saudi Arabia (Ahmed & Martinez-Zarzoso, 2014). India’s total remittances from abroad stand close to US$80 billion per annum, out of which US$10.5 billion come from Saudi Arabia (Rajan, 2020).…”
Section: Saudi Arabia’s Growing Relationship With Indiamentioning
confidence: 99%